2013
DOI: 10.12720/jolst.1.1.75-78
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Air Dosimetry in Some Locations of Jazan Using Passive Track Detectors

Abstract: The concentration of total alpha and radon activities in soil was measured by collecting soil samples at different locations in Jazan. In this study the passive dosimeters which were based on solid state nuclear track detectors SSNTD are reviewed. The principle of passive dosimetry and the factors affecting their performance are discussed. The concentrations of radon and alpha emitters in different locations in Jazan were evaluated using CR-39 detector. The method is based on the proxy equilibrium factor K. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…31,50,51 The radon exhalation values in this study are lower than the values reported for Saudi Arabia. 30,41…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31,50,51 The radon exhalation values in this study are lower than the values reported for Saudi Arabia. 30,41…”
Section: Discussionmentioning
confidence: 99%
“…The average background track density for the unexposed detector was subtracted from the observed values. The value of soil radon concentration (Bq m −3 ) has been obtained from equation (1) 3,6,23,24,30,33 where ρ is the background corrected track density (tracks cm −2 ) and T is the total time of exposure (d). K is the sensitivity factor and its value is calculated by different literatures 3,23,24,30,33 which is 0.2315 tracks cm −2 d −1 (Bq m −3 ) −1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical calculations of the calibration factor, K, were performed by following the model of Eugin Shaji et al (2012), as well as that of Sarma (Barillon et al 1993), for parameters; the fraction of alpha emitters present in air, cup wall dimension, the type of used detector via etching conditions (Sarma 2013;El-Araby 2013). The integrated radon concentration can be calculated from the track density ρ (tracks cm −2 ) which is related to the radon activity concentration C a (Bq cm −3 ) and the exposure time T (days) from formula:…”
Section: The Radioactivity Measurementsmentioning
confidence: 99%
“…Ten attempts (pictures) have been taken for each sample, otherwise to calculate the average number of tracks obtained for each sample. The track density has been calculated by using the following equation [12,13]: (2)…”
Section: Microscopic Viewingmentioning
confidence: 99%